Epidemiology and clinical features of emergency department patients with suspected COVID‐19: Results from the first month of the COVID‐19 Emergency Department Quality Improvement Project (COVED‐2). (16th July 2020) - O'Reilly, Gerard M; Mitchell, Rob D; Wu, Jamin; Rajiv, Prithi; Bannon‐Murphy, Holly; Amos, Timothy; Brichko, Lisa; Brennecke, Helen; Noonan, Michael P; Mitra, Biswadev; Paton, Andrew; Hiller, Ryan; et al.
Abstract: Objective: The aim of the present study was to describe the epidemiological and clinical features of ED patients with suspected and confirmed COVID‐19. Methods: The COVID‐19 Emergency Department (COVED) Project is an ongoing prospective cohort study that includes all adult patients presenting to The Alfred Hospital ED who undergo testing for SARS‐CoV‐2. Current guidelines recommend testing for patients with fevers or chills, acute respiratory symptoms or a high‐risk exposure history, as well as implementation of infection prevention and control precautions for all suspected and confirmed cases. Study outcomes include a positive SARS‐CoV‐2 test result and intensive respiratory support. Results: In the period 1–30 April 2020, 702 of 3453 ED patients (20%; 95% CI 19–22) were tested, with a significant increase during the study period (incident rate ratio 1.019; 95% confidence interval 1.017–1.021, P  < 0.001). The primary outcome of a positive SARS‐CoV‐2 test was recorded in 14 patients (2%; 95% confidence interval 1–3). Shortness of breath (77%), fatigue (100%), myalgia (67%) and diarrhoea (67%) were common among positive cases, while close contact (9%), fever (0%) and healthcare occupation (0%) were not. No positive cases required intensive respiratory support in the ED. Conclusions: The volume of ED patients with suspected COVID‐19 is increasing. Low numbers of positive cases precluded development of accurate predictive tools, but the COVED Project is fulfilling an important role in monitoring the burden of infection prevention and control requirements on the ED. The increasing number of patients meeting isolation criteria has the potential to impact on patient flow and may lead to ED overcrowding. Abstract : The volume of ED patients with suspected COVID‐19 is increasing. Low numbers of positive cases precluded development of accurate predictive tools, but the COVED Project is fulfilling an important role in monitoring the burden of infection prevention and control requirements on the ED. The increasing number of patients meeting isolation criteria has the potential to impact on patient flow and may lead to ED overcrowding.